2008
DOI: 10.1074/jbc.m708098200
|View full text |Cite
|
Sign up to set email alerts
|

The Proprotein Convertase PCSK9 Induces the Degradation of Low Density Lipoprotein Receptor (LDLR) and Its Closest Family Members VLDLR and ApoER2

Abstract: The proprotein convertase PCSK9 gene is the third locus implicated in familial hypercholesterolemia, emphasizing its role in cardiovascular diseases. Loss of function mutations and gene disruption of PCSK9 resulted in a higher clearance of plasma low density lipoprotein cholesterol, likely due to a reduced degradation of the liver low density lipoprotein receptor (LDLR). In this study, we show that two of the closest family members to LDLR are also PCSK9 targets. These include the very low density lipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
347
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 426 publications
(364 citation statements)
references
References 43 publications
14
347
1
2
Order By: Relevance
“…In addition, we showed that LDLR and PCSK9 interact early in the secretory pathway (10) and questioned whether some PCSK9⅐LDLR complex or PCSK9 alone can be targeted directly from the transGolgi network to LE/L, without cycling through the cell surface. Aside from the extracellular pathway, the existence of an intracellular one is supported by the ability of PCSK9 to degrade the LDLR in vivo in the absence of ARH (9) and on the capability of PCSK9-Lamp1 chimeras, which directly traffic to LE/L, to enhance the degradation of the LDLR, VLDLR and apo-ER2 efficiently (26). In liver, ARH seems to be critical for the endocytosis of the extracellular PCSK9⅐LDLR complex (16) but does not seem to play an important role in regulating total levels of endogenous LDLR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that LDLR and PCSK9 interact early in the secretory pathway (10) and questioned whether some PCSK9⅐LDLR complex or PCSK9 alone can be targeted directly from the transGolgi network to LE/L, without cycling through the cell surface. Aside from the extracellular pathway, the existence of an intracellular one is supported by the ability of PCSK9 to degrade the LDLR in vivo in the absence of ARH (9) and on the capability of PCSK9-Lamp1 chimeras, which directly traffic to LE/L, to enhance the degradation of the LDLR, VLDLR and apo-ER2 efficiently (26). In liver, ARH seems to be critical for the endocytosis of the extracellular PCSK9⅐LDLR complex (16) but does not seem to play an important role in regulating total levels of endogenous LDLR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the identification of the R1 domain of AnxA2 that mediates binding to PCSK9 provides a potential new peptidederived tool to regulate PCSK9 function. Derivatives or mimics of this segment could be used to inhibit PCSK9 function on LDLR and possibly on other targets, such as VLDLR or ApoER2 (19). The peptide could also be used to derive a co-crystal structure to better define the CHRD residues, including Gln 554 , seemingly implicated in this interaction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 is the sole PC that is secreted as a catalytically inhibited prosegment⅐PC complex (1, 3,18). Accordingly, the enhanced degradation of the LDLR (3,4,16), very low density lipoprotein receptor (VLDLR), and ApoER2 (19) in endosomes/ lysosomes (14) induced by PCSK9 does not seem to require its catalytic activity (18,20). This intriguing twist in the function of this convertase is supported by the crystal structure of PCSK9, which revealed an extended tight binding complex of the enzyme and its inhibitory prosegment (21).…”
mentioning
confidence: 99%
“…Thus, PCSK9 was first found to enhance the extracellular and intracellular degradation of the closest LDLR family members, namely the VLDLR and ApoER2 (LRP8). 42,43 However, although the interaction of the catalytic domain of PCSK9 with the EGF-A-like domains of these receptors was confirmed, the specific aa in each protein implicated in such interactions are not the same as for the LDLR. For example, in contrast to the LDLR, the GOF D374Y PCSK9 does not degrade these other receptors more efficiently than wild-type PCSK9.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 99%
“…For example, in contrast to the LDLR, the GOF D374Y PCSK9 does not degrade these other receptors more efficiently than wild-type PCSK9. 42 The receptors LDLR, VLDLR, and ApoER2 have been confirmed as PCSK9 target proteins in mice 25,26,65,66 and the LDLR in monkeys 67 and human. 68 Recently, we showed that PCSK9 can enhance the degradation of LRP1 in various cells 44 although proof of this activity in vivo is still lacking.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 99%